PENGARUH INTELLECTUAL CAPITAL TERHADAP BUSINESS PERFORMANCE (Studi Persepsi Karyawan PT BPR Setia Karib Abadi Semarang) - Hayu Mumpuni, Karlina; Raharja, Raharja (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the implementation effect of intellectual capital (human capital, structural capital, and customer capital) to business performance (office-workers perceptiveness case on Limited Company of BPR Setia Karib Abadi Semarang). This research is based on the importance of intellectual capital (human capital, structural capital, and customer capital) to create competitive advantage to go into business performance improvement of PT BPR Setia Karib Abadi Semarang.            The endogenous / dependent variable in this study is business performance and the exogenous / independent variable is intellectual capital (human capital, structural capital, and customer capital). The data in this study consist of the primary data that taken from questionnaires distributed directly to the respondent. Data collected from 38 respondents who are office-workers in various divisions of PT BPR Setia Karib Abadi Semarang. The hypothesis in this study were analyzed using analysis techniques PLS (Partial Least Square) trough the smartPLS software.            The results of this research showed that human capital have negative and no significant impact on business performance,  structural capital have positive and significant impact on business performance, customer capital have positive and significant impact on business performance, meanwhile intellectual capital (human capital together with customer capital and structural capital) have positive and significant impact on business performance.